2020
DOI: 10.1051/alr/2020004
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of shrimp farm sediment by Holothuria scabra: a coupled fatty acid and stable isotope approach

Abstract: Deposit-feeding sea cucumbers are efficient nutrient recyclers and have the potential to contribute to the limitation of organic matter load in polyculture or integrated aquaculture systems. Assessing how they assimilate organic matter originating from other farmed species is therefore important for the development of such multi-species farming systems. Here, a coupled stable isotope − fatty acid approach was used to characterize the assimilation of organic matter from shrimp (Penaeus stylirostris) farming by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Sea cucumbers have previously been proposed as potential bioremediators in integrated aquaculture systems (Zamora, Yuan, Carton, & Slater, 2016); however, while there is evidence that different sea cucumber species vary in their effectiveness (dependent on that species particular physiology) in reducing organic loading from intensive aquaculture systems, the potential benefits from using sandfish in such systems may depend heavily on the culture parameters (i.e., stocking density, individual size) and on the type of culture system. Mathieu‐Resuge et al (2020) used 15 N and 13 C stable isotope (SI) and fatty acid (FA) analysis to track the assimilation of nutrient inputs into sandfish biomass. They reported that sandfish had no impact on the SI or FA composition of shrimp pond sediments, indicating that, while sandfish can derive adequate nutrition for growth from these sediments, they have minimal effect on the remediation of large volumes of pond substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea cucumbers have previously been proposed as potential bioremediators in integrated aquaculture systems (Zamora, Yuan, Carton, & Slater, 2016); however, while there is evidence that different sea cucumber species vary in their effectiveness (dependent on that species particular physiology) in reducing organic loading from intensive aquaculture systems, the potential benefits from using sandfish in such systems may depend heavily on the culture parameters (i.e., stocking density, individual size) and on the type of culture system. Mathieu‐Resuge et al (2020) used 15 N and 13 C stable isotope (SI) and fatty acid (FA) analysis to track the assimilation of nutrient inputs into sandfish biomass. They reported that sandfish had no impact on the SI or FA composition of shrimp pond sediments, indicating that, while sandfish can derive adequate nutrition for growth from these sediments, they have minimal effect on the remediation of large volumes of pond substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of sandfish to feed on and assimilate particulate organic matter from pond sediments makes it a promising candidate for integrated culture with other cultured species (Mathieu‐Resuge et al, 2020; Robinson, Caldwell, Jones, Slater, & Stead, 2015; Slater & Carton, 2009; Slater, Jeffs, & Carton, 2009). In such systems, sandfish, as a secondary crop, would likely benefit from additional organic matter (e.g., uneaten food and feces) generated by intensive aquaculture of a primary fed species, such as fish, crustaceans, or gastropods (Slater & Carton, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotopes have previously been used as trophic markers to investigate sea cucumber ecology (Costa et al, 2014;Slater and Carton, 2010). Coupling biomarkers with fatty acids allows a refined understanding of trophic relationships, especially in polyculture systems (Feng et al, 2014;Mathieu-Resuge et al, 2020). Associating these methods showed differences in sea cucumber composition according to distance from the farm, suggesting differences in food assimilation.…”
Section: Assimilation Of Organic Fish Effluentsmentioning
confidence: 99%
“…Commercially valuable holothurians species most used in IMTA systems include A. japonicus (Zhou et al, 2006;Yuan et al, 2013;Kim et al, 2015), A. mollis (Slater and Carton, 2007;Zamora and Jeffs, 2011, 2012a, 2012b), and P. californicus, (Paltzat et al, 2008, mainly fed with scallops and mussels' biodeposits alone, or mixed with powdered algae (Yuan et al, 2006). Other small-scale experiments used Actinopyga bannwarthi Panning, 1944(Israel et al, 2019 and H. scabra (Mathieu-Resuge et al, 2020).…”
Section: Sea Cucumbers In Integrated Multi-trophic Aquaculturementioning
confidence: 99%